Synchrotron research solves art mystery. Issue 2 (4th March 2017) - Sharp-Paul, Nick
Abstract : An alliance of Australian scientists and conservators has made a quantum leap forward in the analysis of priceless artworks, revealing an earlier painting of a different woman beneath a French Impressionist masterpiece in unprecedented detail, using a technology combination unavailable anywhere else in the world.